2020
DOI: 10.1002/14651858.cd004022.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low sodium diet versus high sodium diet on blood pressure, renin, aldosterone, catecholamines, cholesterol, and triglyceride

Abstract: and it is a condition of accessing publications that users recognize and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commercial gain • You may freely distribute the URL identifying the publication in the public portalIf you believe that this document breaches copyright please con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 279 publications
1
32
0
Order By: Relevance
“…These disparities in risk of and death from either form of stroke in part might explain the slightly larger reductions in incidence and deaths from haemorrhagic stroke observed in our projections. There are ongoing concerns about potential negative sideeffects of whole of populations reduction in salt intake down to 5-6 g/day, citing insufficient evidence (35) and potential unintended consequences to hormones (increased renin, adrenaline, aldosterone) and lipids (36). Most of these concerns are based on observational studies with less robust methods and short-term trials of large salt reductions (37).…”
Section: Comparisons and Implications Of The Findingsmentioning
confidence: 99%
“…These disparities in risk of and death from either form of stroke in part might explain the slightly larger reductions in incidence and deaths from haemorrhagic stroke observed in our projections. There are ongoing concerns about potential negative sideeffects of whole of populations reduction in salt intake down to 5-6 g/day, citing insufficient evidence (35) and potential unintended consequences to hormones (increased renin, adrenaline, aldosterone) and lipids (36). Most of these concerns are based on observational studies with less robust methods and short-term trials of large salt reductions (37).…”
Section: Comparisons and Implications Of The Findingsmentioning
confidence: 99%
“…Studies showed the association between nutritional determinants and overweight/obesity, dyslipidemia, hypertension and T2DM indicating the nutritional intake influences prevalence or prevention for overweight/obesity, dyslipidemia, hypertension and T2DM [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…An increase in salt intake as a matter of fact, have been associated with the risk of developing cardiovascular diseases and stroke [11]. On the contrary, recent studies have expressed concern that reduced sodium intake can lead to an adverse effect on health like unhealthy changes in blood lipids and renal function [12]. Exercise has been found to potentially reduce SBP in hypertensive patients [13].…”
Section: Discussionmentioning
confidence: 99%